Constructive Comments?: Designing an online debate system for the Danish Broadcasting Corporation. (3rd July 2018) - Løvlie, Anders Sundnes
Abstract : This article brings together two strands of research that have the potential to inform the development of constructive forms of journalism: online comments and media design. Through a three-year-long case study of the development of new formats for online comments on the website of the Danish Broadcasting Corporation, I explore the challenges encountered from two perspectives: the design features of the commenting system and the design process. While the broadcaster has emphasized developing features for strengthening editorial control, user engagement has faltered. A lack of attention to users in the design process seems to have contributed to the problems. These findings have implications for constructive journalism's ambitions to facilitate audience engagement, in particular when tied to online platforms.